2020
DOI: 10.1101/2020.06.11.20128652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronavirus and birth in Italy: results of a national population-based cohort study

Abstract: Introduction The study was implemented to provide guidance to decision makers and clinicians by describing hospital care offered to women who gave birth with confirmed COVID 19 infection. Materials and methods National population based prospective cohort study involving all women with confirmed COVID 19 who gave birth between February 25 and April 22, 2020 in any Italian hospital. Results The incidence rate of confirmed SARS-CoV-2 infection in women who gave birth was 2.1 per 1000 maternities at a national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
63
0
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 10 publications
10
63
0
12
Order By: Relevance
“…We noted a higher rate of symptomatic mothers than has been reported in some other studies, 23,24 likely because of selfselection. Our proportion of symptomatic SARS-CoV-2+ mothers in the perinatal period, 62%, is much higher than the 23% reported by the AAP in their registry as of October 3, 2020, 23 but similar to that seen in the Italian Obstetric Surveillance System, 72% on admission, 33 and in one New York hospital system (Presbyterian), 74%, 25 nearly half of whose mothers had their symptoms >2 weeks before delivery. Our rate of SARS-CoV-2+ infants in the first 3 days of life, 7.4%, is higher than the AAP reported rate of 1.7%, 23 the United Kingdom Obstetric Surveillance System, 5%, 34 in the Spanish data, 5.2%, 27 and that seen in the worldwide review of infants of over 660 pregnant women with COVID-19, 4%, 35 but it is consistent with that seen in the Italian data, 6.1%, 33 and in another New York hospital (Elmhurst), 6.7%.…”
Section: Discussionsupporting
confidence: 38%
“…We noted a higher rate of symptomatic mothers than has been reported in some other studies, 23,24 likely because of selfselection. Our proportion of symptomatic SARS-CoV-2+ mothers in the perinatal period, 62%, is much higher than the 23% reported by the AAP in their registry as of October 3, 2020, 23 but similar to that seen in the Italian Obstetric Surveillance System, 72% on admission, 33 and in one New York hospital system (Presbyterian), 74%, 25 nearly half of whose mothers had their symptoms >2 weeks before delivery. Our rate of SARS-CoV-2+ infants in the first 3 days of life, 7.4%, is higher than the AAP reported rate of 1.7%, 23 the United Kingdom Obstetric Surveillance System, 5%, 34 in the Spanish data, 5.2%, 27 and that seen in the worldwide review of infants of over 660 pregnant women with COVID-19, 4%, 35 but it is consistent with that seen in the Italian data, 6.1%, 33 and in another New York hospital (Elmhurst), 6.7%.…”
Section: Discussionsupporting
confidence: 38%
“…The reason for the increasing proportion of severe SARS-CoV-2 in pregnancy compared to the general population is not known and further research is required. In this study we have identified that very few pregnant women (2%) were treated with anti-viral medications, much lower than in some other high resource countries such as Italy where nearly a quarter of women (23%) received treatment with anti-viral agents [22]. Evidence about pharmacological management in the general population is improving [15].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of labor, preterm delivery, CD and emergency CD were more frequent among women with severe COVID-19 requiring hospital admission compared to the 2018 birth population, which corresponds to previous findings (9,13,23). An increasing risk of preterm delivery and CD with increasing severity of COVID-19 has also been reported (14). A previous study from one of the including SE centers found no increased risk of severe outcomes (25), however, they included COVID-19 positive women independently of severity, which might have biased their results.…”
Section: Characteristics Of Women Admitted For Any Reason Are Shown Inmentioning
confidence: 97%
“…Large population-based cohort studies from the United Kingdom (UK) and Italy found an incidence of hospitalization with COVID-19 of 2/1000 maternities (13)(14)(15), which is much higher than the risk of 0.4/1000 deliveries found in DK, FI, IS and NO. However, these studies included admissions for any reason, such as obstetric care and labour.…”
Section: Characteristics Of Women Admitted For Any Reason Are Shown Inmentioning
confidence: 99%
See 1 more Smart Citation